The Influence Of Green Accounting And Financial Technologyon Financial Perfprmance Of MSMEs In Bima City - Nafisah Nurulrahmatiah; Aliah Pratiwi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are key contributors to Indonesia’s economy, yet their financial performance is increasingly influenced by environmental responsibility and technological advancement. This study examines the effect of green accounting and financial technology on the financial performance of MSMEs in Bima City. Using a quantitative explanatory survey approach, data were collected from 210 MSME owners selected through probability random sampling. A structured questionnaire with a six-point Likert scale was employed, and the data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach through SmartPLS 4.0. The findings reveal that green accounting has a positive and significant effect on MSME financial performance, indicating that environmentally responsible accounting practices contribute to cost efficiency, improved business image, and sustainable financial outcomes. In addition, financial technology also has a positive and significant influence on financial performance by enhancing access to financing, increasing transaction efficiency, and supporting more effective financial management. The results further show that green accounting and financial technology jointly explain 64.3% of the variation in MSME financial performance. These findings support stakeholder theory, emphasizing that the integration of sustainable accounting practices and digital financial innovation is essential for improving MSME financial performance and ensuring long-term business sustainability.